Rapid and sensitive noncompetitive immunoassay for detection of aflatoxin B1 based on anti-immune complex peptide. (1st November 2022) - Zou, Wenting; Shi, Ruirui; Wang, Guanqun; Zhao, Zhiling; Zhao, Fengchun; Yang, Zhengyou
Highlights: A phage-peptide against immune complex of nanobody-aflatoxin B1 was obtained. A rapid and sensitive noncompetitive immunoassay for aflatoxin B1 was developed. Enzyme-labeled phage-peptide was prepared to establish direct immunoassay. The whole incubation time of the immunoassay was 10 min. The detection limit of the immunoassay for aflatoxin B1 was 0.006 ng/mL. Abstract: Noncompetitive immunoassays for small molecules are generally considered to be more sensitive than competitive ones. In this study, a phage-peptide against immune complex of aflatoxin B1 (AFB1) and nanobody Nb28 was obtained by phage-display technology. The phage-peptide was labeled with peroxidase and used to develop a direct noncompetitive magnetic-chemiluminescent enzyme-linked immunoassay (Nc-MCLEIA) for AFB1. The 50% signal saturation concentration (SC50 ) and limit of detection (LOD) of Nc-MCLEIA for AFB1 were 0.089 and 0.006 ng/mL, respectively. Compared with competitive immunoassays developed by the Nb28, the sensitivity and efficiency of Nc-MCLEIA were greatly improved. The recoveries of AFB1 from spiked corn, rice, flour, peanut, peanut oil and corn oil samples ranged from 83.8% to 119.2% with coefficient of variable under 8.9%. Furthermore, parallel analysis of natural corn, rice and flour samples by Nc-MCLEIA and HPLC (high performance liquid chromatography) proved that the Nc-MCLEIA was reliable.